Windows 2000 group policy, profiles, and IntelliMirror - Moskowitz, Jeremy (Sybex, 2001)
The Mark Minasi Windows 2000 Series is designed to equip system administrators with in-depth technical solutions to the many challenges associated with administering Windows 2000 in an enterprise setting. The series editor is leading Windows NT/2000 expert Mark Minasi, who selects the topics and authors and develops and reviews each book to ensure that every entry in the series meets your needs and helps you achieve your goals.